Management of Awqaf property, issues and challenges : special reference to Kenya - Utuqa, Salah Jillo (Ahmad Ibrahim Kulliyyah of Laws,International Islamic University Malaysia, 2011)
This study focuses on the institution of waqf from the management perspective with a special reference to Kenya. Because the institution of waqf is very much connected to Shariah, the relevant texts of Qur'an, Sunnah and consensus of the jurists are used to elaborate the waqf rulings. The research relies on inductive method of collecting the opinions of the scholars about waqf, and uses analytical method to discuss the issues and giving preference to some of these opinions. The research has identified that waqf in Kenya faced so many challenges due to poor legal and administrative set-up which may be overcome with sincerity of purpose and a collective responsibility. The researcher calls for implementation of a fully Shariah compatible administration of waqf in the country. Muslim leaders and scholars must be involved in the management of waqf. The field study conducted by researcher reveals that waqf in Kenya is in a pathetic situation which needs urgent address. Moreover, the researcher calls for the democratisation and decentralisation of the waqf institution in the country. The research concludes that the current waqf management infrastructure in Kenya is inadequate and insufficient and a collective effort is required for the institution to regain its role of benefiting the ummah.